PENERAPAN E-GOVERNMENT PADA LAYANAN PAJAK KENDARAAN BERMOTOR DI PROVINSI JAWA TENGAH - Marliyati, Marliyati; Murtini, Sri; Yudhaningsih, Resi; Hasanudin, Mohammad; Gayatrie, Christina Retno (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2022)
Industrial revolution 4.0 which is famous for the phenomenon of disruption of innovation, in the field of government, demands the implementation of information technology systems in the affairs of organizing government services. Electronic applications in the field of government, commonly referred to as e-Government, to optimize the service of certain tasks and functions. Government Resources Management System (GMRS) of Central Java Province, is an integrated system of government of Central Java Province. One of the implementations of the e-Government application available, is the vehicle tax application service, which is named SAKPOLE. The results of the study concluded that the SAKPOLE application for the administration of motor vehicle tax payments had not been fully utilized by motor vehicle taxpayers in Central Java Province. The SAKPOLE application has no effect on motor vehicle tax revenues in Central Java Province.